2007
DOI: 10.1021/bm061236j
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Polypropylene via Surface-Initiated Atom Transfer Radical Polymerization

Abstract: Polypropylene (PP) coated by a non-leachable biocide was prepared by chemically attaching poly(quaternary ammonium) (PQA) to the surface of PP. The well-defined poly(2-(dimethylamino)ethyl methacrylate) (PDMAEMA), a precursor of PQA, was grown from the surface of PP via atom transfer radical polymerization (ATRP). The tertiary ammine groups in PDMAEMA were consequently converted to QA in the presence of ethyl bromide. Successful surface modification was confirmed by ATR-FTIR, contact angle measurement, and an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
277
2
5

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 309 publications
(289 citation statements)
references
References 32 publications
5
277
2
5
Order By: Relevance
“…The majority of these reports also use pDMAEMA as part of a copolymer with other polymers, which may be contributing to its antimicrobial activity. In contrast to our data, some studies have found quaternised pDMAEMA to be effective against the Gram-negative bacteria, E. coli 30,32 . In these reports the bacteria were only incubated with pDMAEMA for 1 hour.…”
Section: Discussioncontrasting
confidence: 99%
“…The majority of these reports also use pDMAEMA as part of a copolymer with other polymers, which may be contributing to its antimicrobial activity. In contrast to our data, some studies have found quaternised pDMAEMA to be effective against the Gram-negative bacteria, E. coli 30,32 . In these reports the bacteria were only incubated with pDMAEMA for 1 hour.…”
Section: Discussioncontrasting
confidence: 99%
“…[41][42][43] Therefore, surface modification of polymeric materials, and particularly of polystyrene and polyolefine surfaces, is of major interest. 16,44,45 To this end, the surfaces of polystyrene and polyolefine slides were dip-coated with PDA and water-soluble AMP 6 was covalently bound to the resulting surfaces. The antibacterial activity of the modified surfaces toward airborne S. aureus was then determined and compared to that of parent PDA-coated surfaces.…”
Section: Resultsmentioning
confidence: 99%
“…There are two main modification methods in the literature: (i) direct copolymerization of either α-olefin [6,7] or polar monomers [8,9] and (ii) chemical modification of preformed polymers [10,11]. For example, antibacterial [12], antifouling [13] and hydrogen storage [14] properties of polypropylene were enhanced via surface-initiated atom transfer radical polymerization [15]. Chlorine atoms on the polymer chains both develop polarity and allow reactive sites for a series of monomer such as acrylates, methacrylates and styrenes [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%